Permanecer SUS: the (re) training in health through the perspective user embracement and humanization - Wilton Nascimento Figueredo; David Ramos da Silva Rios; Priscyla Santana Ferreira Teles; Talita Karen Santos Barros Magalhães; Renata Meira Véras (Universidade Federal de Santa Maria, 2015)
Aim: to analyze the perception of students members of Permanecer SUS program of the Health Secretariat in Bahia, from the National Policy of Humanization. Method: qualitative study of field research with Institutional Ethnography approach. Participant observation and semi-structured interviews were conducted with 10 academics in the health field. Results: the data shows that the program has a positive influence for the participant's academic education. One of the biggest benefits appointed is that there is greater awareness about the principles user embracement and humanization, and consequently a better understanding of the public health system in Brazil. Conclusion: according to the subjects' speech, aspects on the importance of the program for professional formation and recognition of the vulnerability of an integral and humanized care in health services emerged